Water Management Controls Thiacloprid Degradation in Soil via Iron Redox Cycling with Biochar-Supported Zero-Valent Iron - Lin Pan; Shuai Qu; Longfei Liu; Wan Yang; Muhammad Mahroz Hussain; Shengsen Wang (Water, Air, & Soil Pollution, 2026)

Multi-objective optimization of an arc-shaped wave run-up suppression structure for a rounded square column - Meng Shan; Longfei Xiao; Lijun Yang; Lin Yuan; Kelu Li (Ocean Engineering, 2026)

Nonlinear abiotic transformation of a representative organic micropollutant in a deep stratified reservoir: Critical roles of iron and dissolved organic matter - Linlin Wang; Yi Li; Longfei Wang; Li Lin (Water Research, 2026)

Spatio-temporal reconstruction of weak-texture wave fields using thermal stereo vision with active thermal texturing - Lin Yuan; Handi Wei; Longfei Xiao; Deyu Li; Meng Shan (Ocean Engineering, 2026)

Coupled time-domain simulation of hydrodynamic interaction and green water effects on a semi-submersible platform - Rui Qin; Haining Lu; Jianmin Yang; Zhongqin Lin; Longfei Xiao; Qirui Zhai (Ocean Engineering, 2026)

Machine learning uncovers tidal DOM transformations and keystone molecules via FT-ICR MS and reactomics for estuarine nutrient cycling - Guosheng Zhao; Longfei Wang; Yi Li; Jiaying Chen; Lihua Niu; Li Lin (Journal of Environmental Sciences, 2026)

Mechanisms underlying quality deterioration in pre-fermented frozen dough during freeze-thaw cycles: Insights from yeast-dough interactions - Lu Lu; Min Jiang; Ayan Zong; Shuqi Xia; Longfei Yang; Jing Peng; Qinlu Lin (Food Chemistry, 2026)

Effects of sugar alcohols on freeze-thaw tolerance of frozen dough: Focus on ice crystal growth, fermentation properties and gluten aggregation - Longfei Yang; Siwei Wang; Lu Lu; Jing Peng; Huaxi Xiao; Yue Wu; Xinli Yin; Jijun Gong; Qinlu Lin (Food Chemistry, 2026)

Intensification of two-phase toluene nitration by coupling a micro-impinging jet mixer with a microchannel reactor - Bin Wu; Lin Chen; Yanchun Fan; Longfei Yan; Huidong Zheng; Fuweng Zhang (Chemical Engineering Journal, 2026)

Void-fraction-based classification of plunging wave impacts on a surface-piercing column - Wencheng Wu; Longfei Xiao; Lin Yuan; Handi Wei; Yufeng Kou; Hongrui Guo (Coastal Engineering, 2026)

Size-dependent effect of microplastics on sulfamethoxazole degraders in soil as revealed by integration of SIP and metagenomics - Mengke Song; Longfei Jiang; Zhong Lin; Jibing Li; Chunling Luo; Rongliang Qiu (Bioresource Technology, 2026)

Conversion of polyethylene to monoaromatics via a tandem catalytic strategy - Zhiye Ma; Ziyu Cen; Tianrui Bi; Weilong Wen; Cong Luo; Zhijuan Zhao; Baolong Qu; Xiaoyu Zhang; Qinglei Meng; Huizhen Liu; Longfei Lin; Buxing Han (Science Bulletin, 2026)

Spatiotemporal variations in dissolved organic matter chemistry in reservoir-river continuums formed by cascade low-head dams: A case study in southwest China - Fangjie Zhang; Lei Dong; Longfei Wang; Weijie Wu; Yi Li; Li Lin (Journal of Environmental Sciences, 2026)

Giant anomalous Hall and Nernst effects in a heavy fermion ferromagnet - Longfei Li; Shuyue Guan; Shengwei Chi; Jianzhou Zhao; Jiawei Li; Xinxuan Lin; Gang Xu; Shuang Jia (Science Bulletin, 2026)

Building 3D conductive networks within sponge-like porous carbon nanofibers: A CNT-based cathode strategy for superior microbial fuel cells - Wei Huang; Yating He; Wenyi Yan; Longfei Qiao; Yu Tao; Xiangyu Wei; Xiumei Song; Lin Yang; Lichao Tan; Xin Wang; Zhongwei Chen (Chemical Engineering Journal, 2026)

Robust, thermal insulated cellulose porous films for durable and efficient radiative cooling - Xinxin Chen; Mengxiang Dang; Longfei Sun; Yusong Xu; Yu Liu; Lin Liu; Guocheng Zhu; Juming Yao (Carbohydrate Polymers, 2026)

Impacts of hydrological conditions and sediment properties on community structure and activity of phosphorus-transforming microbes in a cascade reservoir system - Fangjie Zhang; Xiong Pan; Weijie Wu; Weiming Tan; Jiayu Guo; Longfei Wang; Li Lin (Journal of Water Process Engineering, 2026)

Disclosing microbial nitrogen metabolism in groundwater via automated machine learning-based analysis: A fluorescence information-based approach - Longfei Wang; Yezhi Yang; Chen Qian; Ziyi Wang; Li Lin; Yi Li (Journal of Environmental Management, 2026)

Study on nonlinear motion, wave run-up and slamming load characteristics of a semi-submersible platform sailing in head waves - Rui Qin; Haining Lu; Jianmin Yang; Zhongqin Lin; Longfei Xiao (Ocean Engineering, 2026)

Clostridium butyricum Promotes Bone Remodeling by Activating Inflammatory Genes in Mice - Yanxin Jia; Longfei Xu; Zijing Ju; Mengze Song; Yonghao Zhou; Bin Li; Fang Wang; Hai Lin; Shuhong Sun; Haifang Li (Probiotics and Antimicrobial Proteins, 2026)

Synergistic design of bioretention cells for efficient inorganic nitrogen removal: Integrating submerged zone, media amendment, and porosity stratification via reactive transport modeling - Longfei Wang; Jie Sun; Guosheng Zhao; Yi Li; Li Lin (Journal of Environmental Management, 2026)

SFG enhances apoptosis of hepatocellular carcinoma by inhibiting tunneling nanotubes-mediated mitochondrial transport in the tumor microenvironment - Shasha Kong; Yuling Liu; Ruying Tang; Hui Li; Hongmei Lin; Longfei Lin (Apoptosis, 2026)

Zero-valent iron embedded biochar-based hydrogel composites for nitrate removal in heterogeneous water-sediment system: Overlooked role of microbial community - Xinnan Pan; Xing Hou; Bian Yao; Li Lin; Wei He; Longfei Wang (Journal of Water Process Engineering, 2025)

Gas-solid dual barrier strategy to efficiently enhance flame-retardancy and smoke-suppression of cellulose aerogel - Xiaolei Luo; Linyue He; Longfei Sun; Xinxin Chen; Lin Liu; Juming Yao; Yurong Cai (Carbohydrate Polymers, 2025)

In-depth investigation of the spatial variations of DOM components in sediments under the influence of cascade dams and their interactions with microbial communities - Fangjie Zhang; Longfei Wang; Xiong Pan; Lei Dong; Weijie Wu; Yi Li; Li Lin (Journal of Environmental Management, 2025)

Generative deep learning model assisted multi-objective optimization for wastewater nitrogen to protein conversion by photosynthetic bacteria - Pengfei Hou; Duofei Hu; Shiqi Liu; Guangming Zhang; Jinsong Liang; Huize Liu; Jizheng Zhang; Xueliang Sun; Dawei Lin; Chengxun Chen; Longfei Liu; Weilin Cai (Bioresource Technology, 2025)

A compact spectroscopic analyzer for simultaneous measurement of N2O, CH4, and CO2 fluxes from soils - Zetong Niu; Longfei Yu; Zhimei Liu; Lifang Wu; Dingxi Chen; Xiaoqing Cui; Tingjung Lin; Yin Wang (Agricultural and Forest Meteorology, 2025)

A prominent oxygenation event in the late Mesoproterozoic broke the calm of the second half of the “Boring Billion” - Lin Meng; Xiaoying Shi; Limin Zhou; Jie Li; Wei Liu; Baozeng Xie; Longfei Sun; Dongtao Xu; Lei Xu; Xinqiang Wang; Dongjie Tang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Enhancing hydrogen sorption kinetics of Ti-based hydrogen storage alloy tanks through an optimized bulk-powder combination strategy - Liansen Bian; Longfei Shao; Bolun Wang; Jiaqi Zhang; Yinghui Li; Zhigang Hu; Jianxin Zou; Kemin Zhang; Xi Lin (Chemical Engineering Journal, 2025)

Exploring the mechanisms of cadmium tolerance and bioaccumulation in a soil amoeba - Yuanchen Zhao; Lin Zhang; Zihe Wang; Chenyuan Wu; Fei Liu; Longfei Shu (Science of The Total Environment, 2025)

Effect of pectin with different esterification degree on the freeze-thaw stability of gluten protein: Structures, functional properties, and Cryoprotective mechanism - Wei Tang; Xinyi Lin; Longfei Ye; Jianfei He; Zhijun Wang; Jianfei Tang; Jianhua Liu; Peicheng Zhao (Food Chemistry, 2025)

The synergistic effect of pulsed red light and leonurus inhibits primary dysmenorrhea induced by oxytocin in mice by modulating calcium signaling and inhibiting inflammatory responses - Qiqi Fu; Hui Jiang; Jiali Yang; Haokuan Qin; Longfei Huo; Yi Ren; Shangfei Lin; Muqing Liu; Jinghui Yao (Journal of Photochemistry and Photobiology B: Biology, 2025)

Experimental investigation on dynamic responses of cantilevered aspirating pipe under the combined action of internal and external flow - Hongrui Guo; Jingjing Li; Mingyue Liu; Longfei Xiao; Lin Guo (Ocean Engineering, 2024)

“Nano knife” for efficient piezocatalytic inactivation of amoeba spores and their intracellular bacteria: Synergetic effect between physical damage and chemical oxidation - Huinan Zhao; Jianyi Zheng; Wei Huang; Zhenzhen He; Fan Huang; Lin Zhang; Tao Zhong; Yadi Li; Dehua Xia; Longfei Shu; Chun He (Journal of Hazardous Materials, 2024)

Using magnesium hydride as the future dual-mode propellant for spacecraft: A simulation investigation - Xi Lin; Ze Zhang; Lianshen Bian; Longfei Shao; Yinglong Kang; Keming Zhang; Jianxin Zou (Chemical Engineering Journal, 2024)

Laboratorial radiative shocks with multiple parameters and first quantifying verifications to core-collapse supernovae - Lu Zhang; Jianhua Zheng; Zhenghua Yang; Tianming Song; Shuai Zhang; Tong Liu; Yunfeng Wei; Longyu Kuang; Longfei Jing; Zhiwei Lin; Liling Li; Hang Li; et al. (Science Bulletin, 2024)

Experimental and numerical investigation on seakeeping performance of a semi-submersible platform navigating in head waves - Rui Qin; Haining Lu; Jianmin Yang; Zhongqin Lin; Longfei Xiao (Ocean Engineering, 2024)

Cellulose nanofiber powered interface engineering strategy to manufacture mechanically stable, moldable, recyclable, and biodegradable cellulose foam - Longfei Sun; Jing Lu; Xinxin Chen; Hanfei Zhao; Lin Liu; Juming Yao (Chemical Engineering Journal, 2024)

Nano- and microplastics drive the dynamic equilibrium of amoeba-associated bacteria and antibiotic resistance genes - Min Zhou; Lu Ma; Zihe Wang; Shicheng Li; Yijun Cai; Meicheng Li; Lin Zhang; Cheng Wang; Bo Wu; Qingyun Yan; Zhili He; Longfei Shu (Journal of Hazardous Materials, 2024)

Modulation of evapotranspiration and stream runoff by weathered bedrock in arid and semi-arid mountains - Pengfei Lin; Peng Zhao; Jian Ma; Junjun Yang; Xi Zhu; Quanyan Tian; Jun Du; Longfei Chen; Zhibin He (Science of The Total Environment, 2024)

Transition of organic matter from allochthonous to autochthonous alters benthic nutrient dynamics via microbial food webs - Nan Yang; Yi Li; Li Lin; Lihua Niu; Wenlong Zhang; Longfei Wang (Science of The Total Environment, 2024)

A MXene heterostructure-based piezoionic sensor for wearable sensing applications - Lin Li; Jiale Pan; Longfei Chang; Zhihao Liu; Guan Wu; Ying Hu (Chemical Engineering Journal, 2024)

Topography-driven differences in soil N transformation constrain N availability in karst ecosystems - Dongni Wen; Lin Yang; Kang Ni; Xingliang Xu; Longfei Yu; Ahmed S. Elrys; Lei Meng; Jinxing Zhou; Tongbin Zhu; Christoph Müller (Science of The Total Environment, 2024)

Soil protists are more resilient to the combined effect of microplastics and heavy metals than bacterial communities - Lu Ma; Lin Zhang; Siyi Zhang; Min Zhou; Wei Huang; Xinyue Zou; Zhili He; Longfei Shu (Science of The Total Environment, 2024)

Soil physical structure drives N-glycan mediated trophic interactions in soil amoebae: Mechanisms and environmental implications - Wei Huang; Yuanchen Zhao; Lin Zhang; Yikun Shi; Zihe Wang; Yingwen Mai; Longfei Shu (Science of The Total Environment, 2024)

Endowing actuators with sensing capability: Recent progress on perceptive soft actuators - Lin Li; Wei Zhang; Zhen Ren; Longfei Chang; Xiaoyong Xu; Ying Hu (Chemical Engineering Journal, 2024)

Determination of uptake rates of volatile organic compounds by 24-hour passive sampling and their application in enclosed ship cabin environments - Tao Yu; Yan Wang; Longfei Chen; Wenjun Leng; Yue Shi; Bencheng Lin; Juntao Zhao; Zhiyuan Wang; Jinhan Mo; Cong Liu (Building and Environment, 2024)

A novel BC/g-C3N4 porous hydrogel carrier used in intimately coupled photocatalysis and biodegradation system for efficient removal of tetracycline hydrochloride in water - Huanjun Zhang; Yanan Yu; Yi Li; Li Lin; Chi Zhang; Wenlong Zhang; Longfei Wang; Lihua Niu (Chemosphere, 2023)

Nanocellulose interface enhanced all-cellulose foam with controllable strength via a facile liquid phase exchange route - Longfei Sun; Lin Liu; Mingbang Wu; Dengfeng Wang; Rongsheng Shen; Hanfei Zhao; Jing Lu; Juming Yao (Carbohydrate Polymers, 2023)

Soil water and salt migration in oasis farmland during crop growing season - Dengke Ma; Zhibin He; Lisha Wang; Wenzhi Zhao; Longfei Chen; Pengfei Lin; Peng Zhao; Wen Wang; Yuan Gao; Jing Li (Journal of Soils and Sediments, 2023)

Response of sap flow in Qinghai spruce (Picea crassifolia) to environmental variables in the Qilian Mountains of China - Jing Fang; Quanyan Tian; Zhibin He; Jun Du; Longfei Chen; Pengfei Lin; Xi Zhu (Trees, 2022)

Impact of climate change on alpine plant community in Qilian Mountains of China - Jun Du; Zhibin He; Longfei Chen; Pengfei Lin; Xi Zhu; Quanyan Tian (International Journal of Biometeorology, 2021)

Daily minimum temperature and precipitation control on spring phenology in arid‐mountain ecosystems in China - Jun Du; Kai Li; Zhibin He; Longfei Chen; Pengfei Lin; Xi Zhu (International Journal of Climatology, 2020)
Climate anomaly has caused substantial shifts in phenology of mountain ecosystems, but the underlying mechanism of phenological responses to climate change is still not well understood. In essence, the abundance of vegetation communities increases the complexity of phenology‐climate relationships, leading to a certain limitation in predictions of future dynamics among different vegetation types using a unified model. In this study, we focused on the climatic constraints on spring phenology in arid mountains (AMs) of China, and emphasis was laid on accurate representation of mechanisms that control phenology across different vegetation types. We Firstly explored spatio‐temporal variations in satellite‐derived estimates of starting date of vegetation growing season (SOS) over the period 2000–2015 using moderate‐resolution imaging spectro‐radiometer (MODIS) normalized difference vegetation index (NDVI). Phenological models in response to climate variability were then established by using mixed‐effect models based on satellite observations and an extensive dataset of climatic measurements. Our results showed that the climatic regulation on SOS varied greatly over vegetation types. More climatic factors that regulate phenological development were found in grassland than forest and shrubland. At ecosystem level, two critical climate factors, daily minimum temperature ( T min ) and precipitation, explained 74–95% of total variability in predicted SOS. The observed sensitivity to T min is expected to be closely linked with the risk of frost damage, while preseason precipitation determines water availability in spring. The varying ecosystem sensitivity revealed the different resilience and adaptability to changing climate among vegetation types, which have been linked to their eco‐physiological characteristics (e.g., water use efficiency) and environmental conditions (e.g., elevation). Overall, our results indicate a strong dependence of spring phenology on T min and precipitation, and create an opportunity for a more realistic representation of vegetation phenology and growth of AM plants in China in land surface models.

Dynamic change in rice leaf area index and spectral response under flooding stress - Qian Sun; Xiaohe Gu; Lin Sun; Guijun Yang; Longfei Zhou; Wei Guo (Paddy and Water Environment, 2020)

Impacts of climate change on reference evapotranspiration in the Qilian Mountains of China: Historical trends and projected changes - Pengfei Lin; Zhibin He; Jun Du; Longfei Chen; Xi Zhu; Jing Li (International Journal of Climatology, 2018)
Global climate change is likely to affect reference evapotranspiration (ET 0 ) and the use of water resources for vegetation management. Our goals were to identify spatio‐temporal characteristics of ET 0 and factors controlling the change in ET 0 and to project spatio‐temporal changes in the Qilian Mountains of China under the future climate conditions. Changes in ET 0 were estimated by the Penman–Monteith method for 22 meteorological stations from 1960 to 2015. We quantified the attributions of climatic factors with the differentiation equation method. Then, we assessed the spatio‐temporal changes in projected ET 0 with CanESM2 model outputs and statistical downscaling model for three representative concentration pathways (RCP) scenarios for years 2016–2100. We found that annual ET 0 averaged across the region was 1001.5 mm, with an insignificant decrease of −0.43 mm/year during 1960–2015. The lowest values were present in the alpine region in the central area, while the highest ET 0 was detected in the western region. An annual and seasonal “evaporation paradox” existed in the Qilian Mountains during the past few decades. Mean daily air temperature measured ( T mean ) and wind speed ( U 2 ) were the dominant factors in ET 0 change. However, the decreasing trend in ET 0 may be due to a diminished effect of T mean triggered by short‐wave radiation ( R s ), actual vapour pressure ( e a ), and wind speed ( U 2 ), but especially by the substantial reduction in U 2 at most stations. Compared with the baseline, ET 0 is likely to increase by 6.31–7.20, 6.11–10.41, and 6.58–17.66%, respectively, under RCP scenarios of 2.6 (very low forcing scenario), 4.5 (medium stabilization scenario), and 8.5 (very high emission scenario), but RCP2.6 ET 0 rates level off and even decline after 2050 while RCP4.5 rates climb only marginally after 2050. Thus, ET 0 projected with the CanESM2 model displayed an upwards trend in the Qilian Mountains, especially the central alpine region.

Functional analysis of PI-like gene in relation to flower development from bamboo (Bambusa oldhamii) - LONGFEI ZHU; YAN SHI; QIAOLU ZANG; QUAN SHI; SHINAN LIU; YINGWU XU; XINCHUN LIN (Journal of Genetics, 2016)

Transcript suppression of TaGW2 increased grain width and weight in bread wheat - Yantao Hong; Longfei Chen; Li-pu Du; Zhenqi Su; Jinfen Wang; Xingguo Ye; Lin Qi; Zengyan Zhang (Functional & Integrative Genomics, 2014)

Molecular Cloning and Expression Analysis of Porcine Ghrelin O-Acyltransferase - Tonghui Lin; Qingyong Meng; Dandan Sui; Dezhi Peng; Yang Li; Xiaofang Liu; Longfei Xie; Ning Li (Biochemical Genetics, 2011)